Peritoneal debulking/intraperitoneal chemotherapy—non‐sarcoma. Issue 1 (24th October 2013) - Kelly, Kaitlyn J.; Nash, Garrett M.; Shaha, Ashok
Abstract The combination of cytoreductive surgery (CRS) and intraperitoneal chemotherapy (IPC) is widely practiced for appendiceal, colorectal, gastric, and ovarian cancers with isolated peritoneal metastasis as well as for primary peritoneal cancer. The aim of this report is to explain the rationale and available techniques for CRS and IPC, and to highlight disease‐specific considerations that should be taken into account when evaluating potential candidates for CRS and IPC. J. Surg. Oncol. 2014 109:14–22. © 2013 Wiley Periodicals, Inc.